Aphasia Following MR Guided Focused Ultrasound Thalamotomy (MRGFUST) Lesioning of The Ventral Intermediate Nucleus (Vim) in A Patient with Essential Tremor (ET): The Importance of Adhering to The Diagnosis of Exclusion Principle and Distinguishing Between Cortical and Thalamic Etiologies - Horowitz, Michael; Saghir, Youseff Al-; Bond, Ronnie; Al-Saghir, Tarek (Cardiology and Cardiovascular Medicine, 2024)
Abstract not available in the source database.